Organic Mental Disorder Accompanied with Anxiety and Depression in Diabetes Mellitus Type 1 - Andrian Fajar Kusumadewi; Cecep Sugeng Kristanto; Inu Wicaksana; Edith Humris Pleyte (Scientia Psychiatrica, 2020)
Introduction: Diabetes mellitus is a chronic disease that is often accompanied by psychiatric disorders. This mental disorder may be caused by the role of biological factors such as neurotransmitter disturbance, or psychological factors of patients who are less prepared to accept changes in conditions caused by this chronic disease. This case report was aimed to present reported cases of mixed anxiety disorders and depression that accompany organic mental disorders post epilepsy and type 1 diabetes mellitus. Case presentation: A girl, 12 years old, living in a rural area with, low socioeconomic background, was taken by her father to a psychiatric clinic with complaints of frequent seizures and feeling depressed and worried, especially when she was disappointed or there was pressure. Patients were also known to have type 1 diabetes mellitus since the previous year. The patient had been hospitalized and was suspected of suffering from atonic focal epilepsy disorders or periodic paralysis. From psychiatric anamnesis, there were depressive feelings, worrying about her mothers and family, and relevant thought progressions. Pharmacotherapy and psychotherapy were conducted to treat this patient. Conclusion: Anxiety disorders and depression are very common in patients with diabetes mellitus and other organic disorders. So clinicians are expected to detect psychiatric disorders early in patients with chronic diseases.